SALVADOR DALI’S ARTISTIC EXPERIMENTS IN THE ART OF JEWELRY AND THEIR IMPACT ON CONTEMPORARY DESIGN - KOLOSNICHENKO, М. V.; KROTOVA, T. F.; REMENEVA , T. V.; PRYKHODKO-KONONENKO , І. A.; CHETVERIK, A. R. (Art and Design, 2022)
The purpose: to analyze the specifics of Dali's creative search for figurative solutions in jewelry; to present a project of jewelry based on the works of S. Dali. Methodology. Historical-typological, analytical, comparative, iconographic methods were applied; during the analysis of Dali’s jewelry works, the methods of formal and figurative-stylistic analysis were applied. Results. The specifics of S. Dali's heritage in jewelry art and its influence on the works of modern masters are analyzed. The specifics of the transformation of a picturesque image into a jewelry work of S. Dali are considered, their material and symbolic features are given. The modern jewelry created on the motives of S. Dali's creativity is considered. The jewelry project "Perfect Speed of Dali" is presented. Scientific novelty. The connection between S. Dali’s works of art and jewelry is revealed and analyzed, the sequence of the artist’s creative search is investigated. The peculiarities of the influence of S. Dali's jewelry projects on the production of modern jewelry are established. Modern jewelry works based on the works of S. Dali have been put into scientific circulation. Practical significance. The materials of this study can be reflected in lecture courses in the disciplines of "Art and Material Culture", "History of Jewelry", and can be a practical basis for the jewelry production.